Effect of STEM-based Learning on the Cognitive Skills Improvement - Firdaus, Anugrah Ramadhan; Rahayu, Galih Dani Septian (Mimbar Sekolah Dasar, 2019)
The success in the modern era is determined by how students strive to have certain skills. This can be achieved by students through the development of cognitive domain, because it is considered as the ability to master subject matter with regard to thinking ability in addition to learning. Hence, this research aims at improving the learning outcomes in the cognitive domain of students at the primary school level. This research was conducted using the Pre-Experiment method with the pretest-posttest One-Group design. The lessons were implemented using Science, Technology, Engineering, and Mathematics (STEM)-based learning, while the learning method was referred to the Engineering Design Process. The stages consist of problem scoping, idea generation, design and construct, design evaluation and re-design. The research involved 30 fourth grade primary school students in Cimahi City as the research samples. The data were collected using observation and analyzed using quantitative descriptive analysis. The research results revealed that there were differences in learning outcomes in the cognitive domain. To conclude, STEM-based learning could improve primary school students' cognitive skills.